The theory of the process in person-centered therapy - Кочарян, Олександр Суренович; Барінова, Наталія Вікторівна (Psychological Counseling and Psychotherapy)
The basic theoretical propositions concerning the process theory in client-centered psychotherapy - its stages, the purpose, the basic properties - are considered in the article. The conclusion is made about the fact that the process represented by C. Rogers hardly describes the psychotherapy itself; it reflects the process of personal growth. The model of the process motion as liberation from “blocking” emotional experiences is presented. The “block” structure and the model of a “capillary blocked with plaques” as well as clinical examples of "organismic flow" liberation are described.